The Correlation of Ig M Anti PGL-1 antibody between blood veins and dryed capillary blood on filter papers in household contact of leprosy patient - Anisha Calista Prakoeswa; Bayu Bijaksana Rumondor; Meva Nareza Trianita; I. Iswahyudi; Fatma Rosida; Linda Astari; M. Yulianto Listiawan; Indropo Agusni; Shinzo Izumi; Medhi Denisa Alinda (PAGEPress Publications, 2019)
Delays of leprosy detection and treatment can lead to disability and potential transmission. Serologic examination has the advantage in detecting Subclinical Leprosy. The procedure of serologic test, which is one of its main limitation, could be simplified by the use filter paper. This study aims to assess the effectiveness of the use of capillary blood dropped on filter paper as a substitute for venous blood in household contact of leprosy patients. Seventeen samples of capillary blood dried on filter paper and venous blood samples from the same individual were examined by ELISA method to determine the levels of IgM anti-Phenolic glycolipid-1 (PGL-1). The mean of anti- PGL-1 IgM levels of filter paper samples 163.31±126.16; whereas the mean of levels from venous samples was 473.16±411.26. There was significant difference and correlation between these two groups. Samples on filter paper in household contact can be used to determine the level of anti-PGL-1 IgM in serum by converting on the regression basis. Further study is required to evaluate the potency of filter paper methods to conduct large-scale serological screening.